The thank you book - Willems, Mo. (New York : Hyperion Books for Children, 2016)
"Piggie is determined to thank everyone she knows, but Gerald thinks she will forget someone important"--Provided by publisher.
May include a thank you card.
0.9
K-3
K-3
330L
Keywords: Gratitude -- Juvenile fiction; Swine -- Juvenile fiction; Elephants -- Juvenile fiction; Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Gratitude -- Fiction; Pigs -- Fiction; Elephants -- Fiction; Animals -- Fiction; Friendship -- Fiction; Gratitude -- Fiction; Pigs -- Fiction; Elephants -- Fiction; Animals -- Fiction; Friendship -- Fiction